1996
DOI: 10.1007/bf00175218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation inferred from RAPD fingerprinting in three species of tilapia

Abstract: This study used random amplified polymorphic DNA (RAPD) fingerprinting for estimating genetic variation and species differentiation in three species of tilapia. A 16-mer random primer generated RAPD markers ranging from 250 to 2400 base pairs (bp). Genetic similarity estimates obtained by pairwise comparisons based on the method of Nei and Li (1979) indicated high genetic similarity (mean genetic similarity (--_ SD), 0.73 (_ 0.15) for Nile tilapia; 0.78 (_+ 0.12) for Mozambique tilapia; and 0.87 (___ 0.07) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…The RAPD technique has been used in the evaluation and identification of the genetic diversities of species and subspecies of tilapia (Bardakci and Skibinski, 1994;Dinesh et al, 1996;Ahmed et al, 2004;Ali et al, 2004;Sherif et al, 2009;Soufy et al, 2009);carps (El-Zaeem et al, 2006); Clarias gariepinus (Saad, et al, 2009); Prochilodus marggravii (Hatanaka and Galetti, 2003); Pimelodus maculatus, P. lineatus, Salminus brasiliensis and Steindachneridion scripta, (Ramella et al, 2006). Similarly, Hassanien et al (2004) found genetic diversity among different populations of Oreochromis niloticus in Egypt using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The RAPD technique has been used in the evaluation and identification of the genetic diversities of species and subspecies of tilapia (Bardakci and Skibinski, 1994;Dinesh et al, 1996;Ahmed et al, 2004;Ali et al, 2004;Sherif et al, 2009;Soufy et al, 2009);carps (El-Zaeem et al, 2006); Clarias gariepinus (Saad, et al, 2009); Prochilodus marggravii (Hatanaka and Galetti, 2003); Pimelodus maculatus, P. lineatus, Salminus brasiliensis and Steindachneridion scripta, (Ramella et al, 2006). Similarly, Hassanien et al (2004) found genetic diversity among different populations of Oreochromis niloticus in Egypt using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The population of Batang Matur is recommended to be used as brood stock in the procurement of stock. As Carvalho (1995) and Dinesh et al (1996) state that generally individuals with greater genetic variation have higher growth rates, developmental stability, viability, fecundity and resistance to environmental stress and diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence was presented that RAPD markers may be useful for systematic investigations at the level of species and subspecies. Dinesh et al (1996) used RAPD fingerprinting for estimating genetic variation and species differentiation in three species of tilapia. A total of 13 RAPD markers differentiating the three species of tilapia were detected.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is important because subpopulations (stocks) may possess novel genetic, physiological, behavioral and/or other characters that promote noticeable variations in lifehistory charaters such as growth rates, fecundity, abundance and disease resistance. Various methods of genetic markers for stock identification and assessment in Nile tilapia have historically been used, including: allozymes (Avtalion et al, 1976;McAndrew and Majumdar, 1983;Basiao and Taniguchi, 1984;Macaranas et al, 1986;Macaranas, et al, 1995;Pouyaud and Agnese, 1995;Rognon, et al, 1996); mitochondrial DNA restriction fragment length polymorphisms (Agnese et al, 1997;Rognon and Guyomard, 1997) and random amplified polymorphic DNA (RAPD) (Bardakci and Skibinski 1994;Naish et al, 1995;Dinesh, et al, 1996;Hassanien et al, 2004).…”
Section: Introductionmentioning
confidence: 99%